Pengaruh Konservatisme Akuntansi Dan Intellectual Capital Terhadap Kualitas Laba - Rosma Rosmawati; Dewi Indriasih (JPA : Journal of Public Accounting, 2021)
Abstract : This journal has several objectives, such as how accounting conservatism affects earnings quality and intellectual capital on earnings quality. Quality is information that affects the company's financial system so as to produce relative financial information. In this case, it aims to see the effect of intellectual capital and accounting conservatism on earnings quality. The type of data used is qualitative data. These variables are Accounting Conservatism X1, Intellectual Capita X2, Profit Quality Y.